Medicinal Plant Images - Cock, I.E. (Pharmacognosy Communications)
Scaevola spinescens (commonly known as currant bush, maroon bush and prickly fanflower) is an endemic Australian plant which is distributed in arid areas of the Australian continent, particularly in the western regions. Australian Aborigines used S. spinescens as a medicinal plant to treat a wide variety of conditions.[1, 2] An infusion of the roots was used to treat stomach pain and urinary disorders. A decoction of the stem was used to treat boils, rashes and skin disorders. Fumes from the whole plant were inhaled to treat viral disorders including colds and influenza. A recent study demonstrated the general inhibitory activity of S. spinescens extracts against RNA viruses using an MS2 phage model system, partially verifying the ethnobotanical usages.[2] Earlier studies have also reported the ability of S. spinescens extracts to inhibit more than 25% of human cytomegalovirus (CMV) late antigen production.[3] S. spinescens also had traditional uses in the treatment of various cancers.[4, 5] Whilst the isolated compounds anticancer activity has yet to be confirmed, studies have indicated that S. spinescens taraxerene pentacyclic triterpenoids may be responsible for this anticancer activity.[6] Photograph was taken by Jeannie Crago of Outback Books and is reproduced here with the authors permission.